(untitled) (مجلة الواحات للبحوث والدراسات, 2021)
One Of The Constant Facts Is That The Existence Of Civil Society Organizations In Any Country Has Exceeded The Concept Of Perception Or Presumption, Even Under The Relatively Old Political Systems, Which Are Considered Part Of Their Structures And Components Against The Concept Of Civil Society Associations And Alike. The Reason Behind That Is Based On What Is Agreed Upon The Content Of Absolute Ruling, And The Lack Of Recognition Of Democratic Practices Through The Components Of Civil Society. Thus, The Latter Has Gone Beyond Its Development, And Even Develop Its Methods Of Dependence To Power And Absolute Support Without An Assessment Of Its Policy, To The Actual And Effective Participation In The Political Decision-Making Process, And Then The Administrative Decision, And With A Kind Of Objectivity To The Extreme, Which Resulted In The Participation Of Civil Society, Organizations In Administrative Management Within The State. Key Words - Civil Society,Democratic,Political Decision, Administrative Management, Administrative Democratic.